The Effects of Uncertainties on Inventory Management of Petroleum Products: A Case Study of Thailand - Roekchamnong, Weerawich; Pornchaiwiseskul, Pongsa; Chiarawongse, Anant (International Journal of Energy Economics and Policy, 2014)
This paper employed a Generalized Autoregressive Conditional Heteroskedasticity in Mean framework to examine (i) the relationship between uncertainty and inventory management, defined as an inventory to sale (IS) ratio; and (ii) the impacts of uncertainties in ex-refinery price, oil funds, and futures price on uncertainty in inventory management, measured as a conditional variance of the IS ratio. Using monthly data for five petroleum products from January 2008 to June 2013, the results indicate that uncertainty induces businesses to hold more of the IS ratio than required. The sensitivity analysis reports that uncertainty in ex-refinery price contributes mostly to the uncertainty in inventory management, while the impact of uncertainty in the oil fund on uncertainty in inventory management is relatively small. Interestingly, the result indicates that uncertainty in futures price can help mitigate uncertainty in inventory management and gives support to the existence of the futures market. Keywords: Petroleum products; uncertainties; inventory management. JEL Classifications: D89; G31; Q41